Strategic Trade Policy in the Presence of International Outsourcing in a Duopoly Model - Simanjuntak, Damiana; Lingga, Doriani (KINERJA, 2017)
This paper analyzes how domestic government sets its optimal export policy in a duopoly model when its domestic firm can only outsource its input while the rival firm is able to both produce and outsource its input. First we analyze the strategic outsourcing behavior of the foreign firm. We find that the foreign firm’s decisions on whether to outsource input or to make it by itself depend on the trade policy taken by the domestic government.  The foreign firm will strategically outsource the entire quantity of its input production to the supplier with an input price higher than its in-house cost, if the domestic firm is subsidized by the domestic government. However, when the domestic firm is being charged a positive export tax by the domestic government, the foreign firm will decide to make input by itself despite the lower input price under the outsourcing regime. From the domestic government’s point of view, we find that the conditions for the foreign firm’s decisions correspond to the domestic social welfare maximization problem. When the foreign firm chooses to outsource its input to the supplier, the domestic government will impose a negative export tax on its firm, namely subsidy. While when the foreign firm chooses to make input by itself, the domestic government will impose an export tax on its firm as trade policy.Keywords: Trade Policy, Export Tax, Subsidy, Outsourcing